Is a COVID-safe Tokyo Olympics and Paralympics really possible? - Dalton, C. B.; Taylor, J. (The Medical Journal of Australia, 2021)
The Olympic games raises manyinfection control, health security and ethical challenges.Japan faces severe challenges in controlling their fourth wave of COVID-19 amidst mounting domestic opposition to the Games. The International Olympic Committees plans appear inadequate and infeasible for the task and there are significant ethical and health security challenges for Japan and Australia as participants in the Games.